Ernst Tugendhat in the Sources of Morality - Wolf, Ursula (Analysis. Journal of Philosophical Research, 2018)
The main moral motive for Tugendhat’s contractualist approach is the desire to be recognized as a member of the contractual community. But this reason can not justify the prohibition of cruelty to animals. With regard to this problem, Tugendhat fluctuates between the adoption of a second motive, compassion, and the externalization of the attitude toward animals and nature as a whole to mysticism. This article attempts to solve this problem by explaining the human-animal relationship and its ethical implications. It is argued that morality generally refers to the consideration of the welfare of beings who are capable of suffering. Since the welfare of these individuals has different dimensions and our relationships with them also have different types, so the moral action is based on different reasons, without having to assume a tension between incompatible motives.